EJNMMI Reports - Giammarile, Francesco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
The European Journal of Hybrid Imaging publishes new basic and clinical research focused on the field of imaging conducted with hybrid or multimodality techniques. Regular features include original research articles, brief communications on novel preliminary approaches, interesting case reports, reviews, guidelines, editorials, and letters to the editor. Educational articles on hybrid imaging modalities and their pre-clinical and clinical applications are also accepted. Review articles provide updates on current applications and issues in the clinical application of hybrid imaging. Guidelines, published by experts from different clinical disciplines, include the clinical, educational and procedural recommendations on the use of hybrid imaging. The unique characteristic of this journal is the focus on hybrid and multimodality imaging technology in different clinical and research fields: oncology, neurology, cardiology, orthopedics, infection imaging.
Keywords: Imaging systems in biology; Nuclear medicine; Biological Imaging; Nuclear Medicine